2015
DOI: 10.1016/j.jjcc.2014.05.001
|View full text |Cite
|
Sign up to set email alerts
|

First direct comparison of clinical outcomes between European and Asian cohorts in transcatheter aortic valve implantation: The Massy study group vs. the PREVAIL JAPAN trial

Abstract: Clinical outcomes after TAVI in the patients included in the PREVAIL JAPAN trial were acceptable and as safe as that of a single-center European cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 32 publications
0
39
3
Order By: Relevance
“…more vascular complications). (9) Secondly, a Japanese study found that their patients had smaller annulus dimensions on multidetector CT as compared with their European counterparts, (10) with implications for prosthesis-patient interactions. We also hypothesised that other factors, such as smaller left ventricular cavity size and increased frailty in Asian populations, may affect the clinical outcomes of TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…more vascular complications). (9) Secondly, a Japanese study found that their patients had smaller annulus dimensions on multidetector CT as compared with their European counterparts, (10) with implications for prosthesis-patient interactions. We also hypothesised that other factors, such as smaller left ventricular cavity size and increased frailty in Asian populations, may affect the clinical outcomes of TAVI.…”
Section: Discussionmentioning
confidence: 99%
“…These include female sex, lower body surface area, and smoking history. Secondly, Asian populations generally have a smaller aortic valve annulus (19,20). In addition, Watanabe et al found that the sinus of Valsalva, sinus of Valsalva height, sinotubular junction, and sinotubular junction height were also smaller in Japanese patients when compared to Western patients, suggesting that these patients had a shallower sinus of Valsalva (19).…”
Section: Anatomymentioning
confidence: 99%
“…First, a limited number of patients were included in this study. However, our registry included the largest number of Japanese patients undergoing TAVI in a real‐world setting compared with the limited indications inherent in previously reported clinical trials . Second, as preprocedural evaluation, such as MDCT or TEE, was performed separately in each individual study center, interobserver variability should be taken into account.…”
Section: Limitationsmentioning
confidence: 99%